Prism adaptation combined with serious games for improving visual-constructive abilities in stroke patients: randomized clinical trial - Massimiliano Oliveri; Massimiliano Oliveri; Massimiliano Oliveri; Sergio Bagnato; Silvia Rizzo; Emilia Imbornone; Patrizia Turriziani; Patrizia Turriziani (Frontiers in Digital Health)
IntroductionVisuomotor adaptation to a displacement of the visual field induced by prismatic lenses can help rehabilitate cognitive deficits when combined with digital cognitive training. The aim of this study was to evaluate the effectiveness of this approach in rehabilitating visual constructive deficits in stroke patients, assess the generalization of improvements to daily living skills, identify which serious games best predicted improvements.MethodsThirty stroke patients were randomly assigned to either a control group, receiving standard rehabilitation, or an experimental group, receiving a therapy combining prism adaptation with cognitive training through serious games over ten consecutive sessions. Patients were administered a neuropsychological test battery at baseline (T0) and after 10 days (T1). Visual constructive abilities were evaluated using Freehand Copy of Drawings and Copy of Drawings with Landmarks tests. Spatial attention was evaluated using Albert's Line Cancellation and Line Bisection tests. Functional abilities were evaluated with the Barthel Index.ResultsTest scores of the Freehand Copy of Drawings improved from T0 to T1 in both the experimental (6.89 ± 2.7 vs. 7.83 ± 2.9; p = 0.01) and the control group (5.84 ± 2.1 vs. 7.51 ± 2.2; p = 0.01). The improvement was comparable between the two groups (p = 0.38). Test scores of the Copy of Drawings with Landmarks improved from T0 to T1 in the experimental (42.94 ± 19.6 vs. 50.2 ± 18.1; p = 0.007), but not in the control group (39.9 ± 19.6 vs. 42.7 ± 20.9; p = 0.41). The improvement was comparable between the two groups (p = 0.28). In the experimental group, Barthel Index scores at T1 correlated with both Free Hand Copy of Drawings scores (R = 0.651; p = 0.009) and Copy of Drawings with Landmarks scores (R = 0.582; p = 0.02). No correlations were found in the Control Group. Serious games targeting attention and motor planning were predictive of improvements in visual construction.Conclusionprismatic lenses combined with digital cognitive training improve visual construction and functional abilities in stroke patients, providing a novel method to promote stroke rehabilitation.